2019
DOI: 10.1371/journal.pone.0213595
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of low-risk skin cancer hospital care towards primary care: A qualitative study on views of general practitioners and dermatologists

Abstract: BackgroundRising healthcare expenditures places the potential for substitution of hospital care towards primary care high on the political agenda. As low-risk basal cell carcinoma (BCC) care is one of the potential targets for substitution of hospital care towards primary care the objective of this study is to gain insight in the views of healthcare professionals regarding substitution of skin cancer care, and to identify perceived barriers and potential strategies to facilitate substitution.MethodsA qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 58 publications
(45 reference statements)
0
27
0
Order By: Relevance
“…This might be explained by fewer TBSEs performed by GPs (although strongly encouraged in the DOTP) and/or previously shown lower diagnostic skills in diagnosing (pre)malignant skin lesions compared with dermatologists 5. Lack of time in primary care could be a factor contributing to the above‐mentioned points for improvement 9,21. Obviously, transfer of SC care puts more pressure on primary care and a sufficient amount of time, finances and healthcare providers seems essential to facilitate this.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This might be explained by fewer TBSEs performed by GPs (although strongly encouraged in the DOTP) and/or previously shown lower diagnostic skills in diagnosing (pre)malignant skin lesions compared with dermatologists 5. Lack of time in primary care could be a factor contributing to the above‐mentioned points for improvement 9,21. Obviously, transfer of SC care puts more pressure on primary care and a sufficient amount of time, finances and healthcare providers seems essential to facilitate this.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed GPs and dermatologists to be generally positive about this transfer of care. 9 At the beginning of the project, regional guidelines were drawn up concerning the diagnostics and treatment of (pre)malignant skin lesions in primary care, and when a GP should refer a patient to a dermatologist (Appendix S1; see Supporting Information). These regional guidelines were based on existing (inter)national guidelines.…”
Section: The Dermato-oncological Training Programmementioning
confidence: 99%
See 2 more Smart Citations
“…Skin cancer is often managed in primary care and specialties without the involvement of dermatologists [3]. It is common practice to excise lesions suspicious for skin cancer without prior histological confirmation.…”
Section: Introductionmentioning
confidence: 99%